Application of laser scanning microscopy for the analysis of oral biofilm dissolution by different endodontic irrigants - Aldo del Carpio-Perochena; Clovis Monteiro Bramante; Marco Antonio Hungaro Duarte; Flaviana Bombarda de Andrade; Bruno Cavalini Cavenago; Marcelo Haas Villas-Bôas; Ronald Ordinola-Zapata; Pablo Amoroso-Silva (Wolters Kluwer Medknow Publications, 2014)
Background: Multi-specie biofilms are highly resistant to antimicrobials due to cellular interactions found in them. The purpose of this study was to evaluate, by confocal laser scanning microscopy, the biofilm dissolution effectiveness of different irrigant solutions on biofilms developed on infected dentin in situ. Materials and Methods: A total of 120 bovine dentin specimens infected intraorally (30/group) were treated by the following solutions: 2% of chlorhexidine digluconate, 1%, 2.5% and 5.25% of sodium hypochlorite (NaOCl). The solutions were utilized for 5, 15 and 30 min with 2 experimental volumes 500 μL and 1 mL. All the samples were stained using an acridine orange and the biofilm thickness before (control group) and after the experiments were evaluated, utilizing a confocal microscope at ×40. The Mann-Whitney U and the nom-parametric Kruskal-Wallis Dunns tests were utilized to determine the influence of the volume and to perform the comparisons among the groups respectively. The significance level was set at P < 0.05. Results: Statistical differences were not found among the control and the 2% chlorhexidine digluconate groups at any experimental period (P > 0.05). The biofilm dissolution treated with 1% NaOCl was directly proportional to the exposure time (P < 0.05). The higher values of biofilm dissolution were found in 2.5% and 5.25% NaOCl groups (P > 0.05). Conclusion: The higher exposure times and concentrations of NaOCl were not sufficient to dissolve 100% of the biofilm. However, all NaOCl solutions were more effective than 2% chlorhexidine digluconate to dissolve organic matter.